DESAIN UI/UX HALAMAN LOGIN WEB MENGGUNAKAN FIGMA DENGAN PENDEKATAN DESAIN BERPUSAT PADA PENGGUNA - Aditya Pratama Putra; M Zaky Zikriandika; Helmina Helmina (Jurnal Informatika, Sistem Informasi dan Kehutanan (FORSINTA), 2025)
The development of information and communication technology has driven the importance of effective user interface (UI) and user experience (UX) design in website development. The login page is one of the main components that plays a crucial role as the user's initial access to the system, so a design that provides comfort, convenience, and security is needed in its use. This study aims to design a UI/UX design for a web login page using the Figma application with a User-Centered Design (UCD) approach. The UCD method is used because it focuses on user needs, characteristics, and experiences throughout the design process. The research stages include identifying user needs, analyzing problems, creating wireframes, creating prototypes, and evaluating the design. The resulting design displays a simple, responsive, modern, and easily understood interface for users.